Reactivation of Kamb Ice Stream tributaries triggers century‐scale reorganization of Siple Coast ice flow in West Antarctica. Issue 20 (21st October 2015) - Bougamont, M.; Christoffersen, P.; Price, S. F.; Fricker, H. A.; Tulaczyk, S.; Carter, S. P.
Abstract: Ongoing, centennial‐scale flow variability within the Ross ice streams of West Antarctica suggests that the present‐day positive mass balance in this region may reverse in the future. Here we use a three‐dimensional ice sheet model to simulate ice flow in this region over 250 years. The flow responds to changing basal properties, as a subglacial till layer interacts with water transported in an active subglacial hydrological system. We show that a persistent weak bed beneath the tributaries of the dormant Kamb Ice Stream is a source of internal ice flow instability, which reorganizes all ice streams in this region, leading to a reduced (positive) mass balance within decades and a net loss of ice within two centuries. This hitherto unaccounted for flow variability could raise sea level by 5 mm this century. Better constraints on future sea level change from this region will require improved estimates of geothermal heat flux and subglacial water transport. Key Points: Modeled restructuring of the Siple Coast ice streams replicates past flow features Kamb Ice Stream tributaries are the source of regional ice flow instability Reduced regional mass balance could increase sea level by 5 mm in 100 years